2004
DOI: 10.1016/j.jcrs.2003.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Legacy AdvanTec and Sovereign WhiteStar

Abstract: There was less increase in wound temperature over time with the S-WS than with the L-ADV system in sleeved and unsleeved simulated surgery in human eye-bank eyes. Because the ultrasound handpieces respond differently under different load scenarios, meaningful comparisons of pulsing features are difficult to create.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…The Legacy Advantec has been documented to be hotter than the Sovereign, even adjusting for duty cycle differences when the instruments were twisted in the wound. 7 This would occur at 430 g of weight. Clearly, more clinical work must be done to correlate in vitro weights with the clinical situation; however, these examples indicate the frictional forces associated with torqueing or pressing the phaco tip against the wound may be substantial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Legacy Advantec has been documented to be hotter than the Sovereign, even adjusting for duty cycle differences when the instruments were twisted in the wound. 7 This would occur at 430 g of weight. Clearly, more clinical work must be done to correlate in vitro weights with the clinical situation; however, these examples indicate the frictional forces associated with torqueing or pressing the phaco tip against the wound may be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Miller, ''Temperature of Phaco Tip Is a Function of Ultrasound Power Management and Fluid Flow,'' EyeWorld February 2004, pages [4][5]. 7 This means in a minimal workload environment (such as water), the Sovereign has a dynamic range about 2.3 times greater than the Legacy Advantec. If this inherent bias is appropriately controlled, the results will be the same for both machines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laboratory studies have shown that despite a bare phaco needle, rapid on-off cycling of ultrasonic power can prevent the temperature during bimanual microincisional surgery from rising above 45 C, the level that is considered the threshold for corneal damage. [1][2][3][4][5] A study in human cadaver eyes demonstrated that the Millennium Microsurgical System (Bausch & Lomb), with conventional power settings, can be used safely to perform bimanual sleeveless phacoemulsification. 4 The current study was undertaken to assess whether software allowing precise, customizable microburst and hyperpulse power modulationsdwith bursts of phaco power as short as 4 msdfurther reduces wound temperatures during sleeveless bimanual phacoemulsification in general, but specifically with the Millennium.…”
Section: J Cataract Refract Surg 2006; 32:639-642 Q 2006 Ascrs and Escrsmentioning
confidence: 99%